A Study on the Burpee Exercise Influence on the Endurance Indicator and Attention in School Children: Life Sciences-Physical education - Polevoy, Georgiy; Egorycheva, Elina; Fedorov, Aleksandr; Elamin, Moussa Mohammed (International Journal of Life Science and Pharma Research, 2023)
Burpee is a well-known physical exercise all over the world. However, its effects on physical abilities have yet to be studied. The study aims to determine the impact of the Burpee exercise on the endurance and concentration of children aged 15-16. Inclusion criteria Age - 15-16 years, gender - boys, and girls. Schoolchildren in the control group were engaged in a standard physical education program at school, and children from the experimental group additionally performed burpee exercises. Endurance indicators were determined by the test running a distance of 2 kilometers (Running 2 km). The Bourdon test determined indicators of concentration of attention in children. The study used the T-criterion tests. During the study period, the level of endurance development improved by only 1.9% (p>0.05), and the concentration indicators improved from 72.2±5.8 to 75.5±6.1 (p>0.05). A slight increase in the indicators in both tests in the control group can be explained by the natural increase in the indicators of schoolchildren over four months and the effectiveness of using the standard physical education program at school. In the experimental group (9th grade), the indicators in both tests significantly (significantly) improved. Endurance of schoolchildren increased by 9% (p<0.05), and concentration indicators improved from 73.2±4.9 to 86.6±6.2 (p<0.05). Each student’s physical load should be individual when performing the Burpee exercise. If 15-16-year-old schoolchildren perform "Burpee" exercises in physical education classes, then to a significant extent, the indicators of endurance and concentration will significantly improve.